Implementation of Problem-Based STAD Learning to Improve Students’ Critical Thinking Skills on Ecosystems - Alfina Nuril Lailia (PT Ahan Group Publisher, 2025)
This study investigates whether the Problem-Based Student Teams Achievement Division (STAD) learning model can enhance students’ critical thinking skills to a greater extent than conventional lecture-based instruction on the topic of Human Impact on Ecosystems. A quasi-experimental method was employed, using test items as the research instrument. A total of 31 seventh-grade students from class VII I served as the control group, while 30 students from class VII G constituted the experimental group. Descriptive analysis was used to describe the post-test results for each indicator of critical thinking skills. An independent t-test was then conducted to examine the differences in essential thinking abilities between the experimental and control groups. Additionally, an N-gain test was conducted to assess the magnitude of improvement in students’ critical thinking skills in the experimental group relative to the control group. The findings indicate that the Problem-Based STAD learning model improved students’ critical thinking skills in the experimental group at a moderate level, with an N-gain score of 0.43. In contrast, the conventional learning approach led to a low level of improvement, with an N-gain score of 0.24. This study emphasises the implementation of a problem-based STAD model derived from students’ real-life issues, making the learning process more contextual. The topic of Human Impact on Ecosystems was chosen for its strong relevance to students' everyday experiences.